2022
DOI: 10.1038/s41598-022-12173-w
|View full text |Cite
|
Sign up to set email alerts
|

The effects of response inhibition training following binge memory retrieval in young adults binge eaters: a randomised-controlled experimental study

Abstract: Binge eating is increasingly prevalent among adolescents and young adults and can have a lasting harmful impact on mental and physical health. Mechanistic insights suggest that aberrant reward-learning and biased cognitive processing may be involved in the aetiology of binge eating. We therefore investigated whether recently developed approaches to catalyse brief interventions by putatively updating maladaptive memory could also boost the effects of cognitive bias modification training on binge eating behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…Several research groups have utilized computerized cognitive training to address EF to reduce binge eating and eating disorder pathology ( Boutelle et al, 2016 ; Brockmeyer et al, 2019 ; Chami et al, 2022 ; Das et al, 2022 ; Giel et al, 2017 ; Turton et al, 2018 ). These interventions often use a repetitive task (e.g., Go/NoGo, dot-probe) to increase inhibition toward food cues or direct attention away from food cues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research groups have utilized computerized cognitive training to address EF to reduce binge eating and eating disorder pathology ( Boutelle et al, 2016 ; Brockmeyer et al, 2019 ; Chami et al, 2022 ; Das et al, 2022 ; Giel et al, 2017 ; Turton et al, 2018 ). These interventions often use a repetitive task (e.g., Go/NoGo, dot-probe) to increase inhibition toward food cues or direct attention away from food cues.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed promising preliminary effects at reducing binge eating ( Boutelle et al, 2016 ; Brockmeyer et al, 2019 ; Chami et al, 2022 ; Giel et al, 2017 ), although sample sizes were small and maintenance effects were not durable. Despite these positive studies, others have failed to show any effect ( Das et al, 2022 ; Turton et al, 2018 ). Computerized training programs have been criticized for their lack of generalizability to real-world behavior outside of a laboratory.…”
Section: Introductionmentioning
confidence: 99%